SOSIALISASI PENGGUNAAN MEDIA PEMBELAJARAN VISUAL PADA EXPLORE PETA GEOGRAFIS INDONESIA DI SEKOLAH DASAR - Fauzia, Arisna; Iswahyudi, Iswahyudi; Mulyani, Cut; Insiyah, Zulfa Raodhotul; Fahrizal, Erlan; Febriani, Alia; Faizah, Annisa Nu; Husnia, Fadillah; Zahra, Indi; Hermansyah, Aldy (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2024)
The Independent Student Exchange Program (PMM) Batch 4 requires students to participate in community social contribution activities with their lecturers. The author took the theme of this activity to be related to learning media in schools. One activity that can be carried out is supporting teaching activities in the Social Science Subject, namely introducing the islands of the archipelago. Indonesia is an archipelagic country with various islands and strategic areas. Indonesia's geographic location is in southeast Asia, bordering Malaysia, Brunei Darussalam, Singapore, the Philippines and the South China Sea. Because of this geographical position and location, Indonesia is a huge country experiencing the expansion of provinces. As per its development, Indonesia has 38 provinces spread from Sabang to Merauke. This social contribution activity aims to introduce and disseminate educational and interesting learning media to students about the Province and the beautiful islands in Indonesia. This service method uses teaching materials in the form of interactive Pop-up Books. The learning media presented also includes media with 3-dimensional visualisation so that students can increase their motivation to learn related subjects. This activity was conducted for elementary school teacher participants and 4th-grade students. At the end of the activity, it is hoped that participants will always be aware of developments in Indonesian geographical map material with interesting learning.